E-Government Policy Study on Service Quality in Soppeng Regency - Hariadi, ‎; Susanti, Gita; Rusdi, Muhammad (KnE Social Sciences, 2025)
The rapid development of technology and information has made the government adapt by transforming to the electronic government (e-Government) system. The transformation of governance is towards a good governance system, namely, good governance, more modern, transparent, and accountable. The purpose of this study is to find out the extent of the quality of e-Government services provided by government institutions based on the public perspective, especially on the KIM formed by the Department of Communication and Information. Qualitative descriptive methods of secondary data sources were used, such as studies of literature, journals, articles and documents, and regulations related to this policy. The results of this study illustrate that the implementation of e-government from the perspective of public services is still not optimal, this is evident as it has not significantly increased public participation, especially in technology-based public services.